USE OF ANTIBIOTICS IN THE PRESERVATION OF PRAWN - SURENDRAN, P K; IYER, K MAHADEVA (Fishery Technology, 2025)
Effect of incorporating chlorotetracycline (CTC) in ice upto 5ppm level on the keeping quality of prawns has been studied. A shelflife extension by nearly six days is obtained for the CTC-iced sampleover the control. The headless prawns absorbed greater amounts ofCTC than whole prawns during storage in. CTC-ice. Traces of theantibiotic are found in the muscle of the CTC-iced prawns even aftercooking for one hour. The cause of destruction of CTC when usedfor prawn preservation is discussed.